"Democracy Is Always Going to Be Hard": An Interview with Charles Taylor. Issue 2 (2022) - Costa, Paolo
Abstract: This interview with the Canadian philosopher Charles Taylor was designed and realized to celebrate his ninetieth birthday in November 2021. The interview touches on all the main themes of Taylor's oeuvre, from his view of philosophy to the inherent link between human intelligence and strong evaluations, from the Immanent Frame to postsecularity, from today's democratic crisis to the 1980s debate between liberals and communitarians, from Xi Jinping's China to the global health emergency, from spirituality to Philosophical Romanticism. It is both a hindsight analysis by a first-class thinker and a glance into the future by an incurable optimist.